L’apport de la géomatique à la connaissance de la partie terminale de l’aqueduc du Gier à Lyon - Éric Leroy (Gallia)
Interest in Lyon’s aqueducts, and in the Gier aqueduct in particular, goes back a long way. The general route of the Gier aqueduct is well known. However, its mapping on a regional scale masks certain uncertainties which can only be observed through analysis at a more local scale. Here, we propose to evaluate the contributions of geomatics, analysis and spatial modelling to the study of the aqueduct route. By bringing together and re-examining various sources, old and recent, at different scales, we attempt to specify the route of the aqueduct and its various sections, to complete a ground plan and to analyse in detail the level of water flow. The present study concerns the terminal section of the route of the Gier aqueduct on the approach to Lyon (Rhône). In total, 23 sites were explored in the course of this study. The available documentation was compiled and processed within the municipal archaeology department’s Geographic Information System (GIS), known as Alyas (Lyon Archaeology and Spatial Analysis).The aqueduct generally follows a straight line in the part of the route that interests us, but the topography also demands more sinuous underground sections. The more granular scale enables us to propose several possible routes, consisting of a succession of straight sections linked by fairly sharp bends. We can assume that this pattern made it easier to adapt to the terrain than would the construction of long curved sections. The aerial sections are more rectilinear, since they are not constrained by the terrain. Analysis of the cadastral map, both Napoleonic and current, clearly shows the alignment of the plots with the elevated hydraulic structure. It is thus possible to suggest alternative routes based on road or plot boundaries. In the case of the siphons, because of the absence of traces on the ground, the tendency is to assume they consist of long rectilinear sections. However, topographic analysis and the orientation of certain structures showed variations in their layout.The aqueduct adapts to the topography, following the contour lines, using buried pipes to pass through elevated spaces, crossing depressions by means of overhead passages, walls and rows of arches. But other techniques are also employed, with tunnels running through some hillocks and siphons used to cross deep valleys. This succession of structures was complemented by a local scale analysis of altimetric data, which made it possible to locate with greater certainty the transitions between buried and aerial sections and between walls and bridges. By providing information on the manholes uncovered, we were also able to estimate the location of other structures of this type because of the regular pattern of positioning, and adjust the layout of the aqueduct accordingly. Although the construction, dimensions and general profile of the aqueduct are broadly standardised, irregularities can be observed in the details, particularly in the dimensions of the channel. It can be assumed that this variation was a response to local course constraints, for example a widening of the internal channel in order to reduce the rate of flow before a bend. The piers of the bridges and the openings of the arches are calibrated, their measurements regular and known. This regularity made it possible to situate the missing piers. In order to maintain a regulated flow rate, the average slope of the cunette is regular and not very steep. Over the entire route, it was calculated to be about 0.11%, or 1.1 m per km, but many “irregularities” –counter-slopes and accelerations– were observed locally. Pronounced changes in channel direction would explain the counter-slopes which, often located before a bend, served to slow the flow and avoid excessive wear on the pipe.What we know about the aqueduct has been refined through new research: the re-examination of historical surveys and recent developments in analysis and spatial modelling tools have thus made it possible to complete the reference model by confirming differences in local scale, in the shape of the structure and in its layout. We argue that these variations are explained by the need to adapt to local topographic constraints and concerns and by ease of construction. (Traduction Fanny LABADIE)